Water Quality Analysis at Sungai Lumut Kiri and Floating Rubbish Problem - Zulkifli, Muhammad Amirhanafi (Universiti Teknologi PETRONAS, 2020)
A river is one of the important sources of fresh water. Due to the highly paced industrial development leads to worsen of water pollution problem. Lumut Kiri River is one of the important rivers in Perak for water supply. By having affected by the discharged of agricultural waste from 2 nearby premises caused the river to be polluted in recent years. The color of the river is black and produced an unpleasant smell tin that area. The purpose of this study is to perform water quality analysis tat Lumut Kiri River streams. The samples were taken at the river and been tested In-Situ by using YSI ProDSS Multimeter for certain parameters such as pH, Salinity, Temperature, Conductivity and Dissolved Oxygen contained tin the water sample and the remaining parameters tare conducted at Universiti Teknologi PETRONAS lab to measure for BOD, TSS, COD and Ammonia. All the data gathered and were analyzed very precisely.